2022
DOI: 10.3390/fermentation8080367
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Metabolism of Lacticaseibacillus casei and Lactobacillus kefiri Isolated from Qymyz, a Traditional Fermented Central Asian Beverage

Abstract: The growth characteristics of two strains of lactic acid bacteria (LAB), Lacticaseibacillus casei and Lactobacillus kefiri, isolated from qymyz, a traditional fermented mare milk beverage, were studied and modeled, including the effect of different carbohydrates, pH, and temperature. Along with population, substrates, and metabolites, lactic acid and ethanol were monitored by HPLC. Growth parameters were obtained from mono- and biphasic logistic growth models that fit the population evolution of L. casei and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In general, the results showed that the population obtained in a synthetic medium was similar to that obtained in reconstituted mare milk. Figure 5A,C shows that LAB simulated population obtained with the monoculture growth parameters obtained by Kondybayev et al [15] fitted well with the experimental population of LAB in coculture. This means that the LAB population growth rate and final population was not significantly affected by the coculture with K. unispora.…”
Section: Resulting Parameters Of Modelssupporting
confidence: 64%
See 3 more Smart Citations
“…In general, the results showed that the population obtained in a synthetic medium was similar to that obtained in reconstituted mare milk. Figure 5A,C shows that LAB simulated population obtained with the monoculture growth parameters obtained by Kondybayev et al [15] fitted well with the experimental population of LAB in coculture. This means that the LAB population growth rate and final population was not significantly affected by the coculture with K. unispora.…”
Section: Resulting Parameters Of Modelssupporting
confidence: 64%
“…Lactose consumption in mono-and coculture followed the same trend for L. kefiri. Among the studied LAB, only L. kefiri produces ethanol [15]. The content of ethanol in the L. kefiri coculture reached ~7.8 g•L −1 , which was the same level as in the monoculture of this strain.…”
Section: Lactic Acid and Ethanol Productionmentioning
confidence: 64%
See 2 more Smart Citations
“…The microbial composition of raw mare milk, like that in other similarly less common milk types, has not been studied in depth: nevertheless, it is known to be widely variable, depending on many factors, such as the breed, season, and region [34]. However, many studies regarding the microbiological composition of fermented mare milk are available.…”
Section: Microorganisms In Fermented Mare Milk Productsmentioning
confidence: 99%